O agente indígena de saúde e o uso da tecnologia no atendimento obstétrico - Maia, Janize Silva [UNIFESP] (2019)
Introduction: Information is the essence of health professional’s work. Despite the restructuring of care system for indigenous people’s health in Brazil, indicators still remain unfavourable, encouraging research on the use of technologies in a study focused on the indigenous population, identifying the potential use of technologies for improving care, health status and well-being through empowerment of the indigenous health agent (IHA). Objective: Develop and evaluate a mobile application for using by IHA during obstetric care. Matherials and methods: Applied research of quantitative approach technology production, designed to develop an application for a mobile device, for the purpose of providing information about risk factors in pregnancy and guidelines based on the gestational age reported to the IHA. Results: The application was developed using the Scrum method, in an adapted way, where the Product Owner, the Scrum Master and the Dev team were replaced by the author, who commanded the programming and was responsible for the product backlog, and the programmer, whose responsibility for coding resulted in sprint backlogs. The application was assessed by a group of experts and IHA using Nielsen heuristics. The inserted content was evaluated by health professionals and proved to be suitable. In addiction, it was conducted a detailed study of specialists answers for each question. The lack of identification of low and high priority problems by most IHA reinforce the agreement among the different evaluators that the instrument provided access to information, which until then was only available through verbal contact with other professionals of the team for indigenous health. Conclusion: The application was developed for utilization by the IHA, explaining risk factors that can evidence an unfavourable evolution of pregnancy, and has undergone technical and functional quality assessments, including page loading speed, content, user first impression, information reliability or accuracy, ease of navigation and updating, and interactivity. Thus, it is considered that the objectives of development and evaluation of the application as a support instrument for the assistance provided by specialists and IHA were achieved as demonstrated by the results presented.